Gas Monitoring of Volcanic-Hydrothermal Plumes in a Tropical Environment: The Case of La Soufrière de Guadeloupe Unrest Volcano (Lesser Antilles) - Moune, Severine; Moretti, Roberto; Burtin, Arnand; Jessop, David Edward; Didier, Tristan; Robert, Vincent; Bonifacie, Magali; Tamburello, Giancarlo; Komorowski, J-Christophe.; Allard, Patrick; Buscetti, Margaux (Frontiers in Earth Science, 2022)
Fumarolic gas survey of dormant volcanoes in hydrothermal activity is crucial to detect compositional and mass flux changes in gas emissions that are potential precursors of violent phreatic or even magmatic eruptions. Here we report on new data for the chemical compositions (CO2, H2S, SO2) and fluxes of fumarolic gas emissions (97–104°C) from La Soufrière volcano in Guadeloupe (Lesser Antilles) obtained from both mobile MultiGas measurements and permanent MultiGas survey. This paper covers the period 2016–2020, encompassing a period of enhanced hydrothermal unrest including an abrupt seismic energy release (M 4.1) on April 27, 2018. Our dataset reveals fumarolic CO2/H2S and SO2/H2S gas trends correlated to the evolution of surface activity and to other geochemical and geophysical parameters. We demonstrate that, even under tropical conditions (high humidity and rainfall), MultiGas surveys of low-T fumarolic emissions permit to distinguish deeply sourced signals of volcanic unrest from secondary changes in degassing due to shallow forcing processes such as water-gas-rock interactions in the hydrothermal system and meteorological effects.